Polyurea-ceramic composite coating for leading edge of wind turbine blade and preparation method thereof

By compounding polyaspartate polyurea with ceramics to form a polyurea-ceramic composite coating, the problem of easy damage to the leading edge of wind turbine blades is solved, and the coating effect is achieved with high weather resistance, rain erosion resistance and wear resistance.

CN117050626BActive Publication Date: 2025-01-21XIAN THERMAL POWER RES INST CO LTD +1

Patent Information

Application Number
CN202311090248.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-01-21
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

The leading edge of wind power blades is prone to cracking, debonding and cracking. The existing coating materials are not resistant to rain corrosion, high and low temperatures and weather resistance.

Method used

The polyaspartate polyurea base material is compounded with ceramics to form a polyurea-ceramic composite coating. The hardness and toughness of the coating are enhanced through the three-dimensional network cross-linked structure of ceramics and the polymer chains of polyurea.

Benefits of technology

It significantly improves the rain erosion resistance, impact resistance and adhesion of the coating, extends the service life of the blade leading edge, and improves wind power generation efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a polyurea-ceramic composite coating for the leading edge of a wind turbine blade and a preparation method thereof. The coating comprises aspartic acid ester polyurea and ceramics. The ceramics have good strength and hardness, and can improve the hardness and toughness of the coating as a whole, and improve the overall anti-rainwater erosion performance of the coating. Specifically, the polyaspartic acid ester polyurea is made of polyetheramine, diisocyanate, polyaspartic acid ester resin and isocyanate as raw materials, and the polyetheramine is a hydrophilic monomer, so that the system has good hydrophilicity, which is conducive to forming a water film on the leading edge surface of the wind turbine blade, and effectively buffering the impact of raindrops on the leading edge of the wind turbine blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wind power generation, and in particular relates to a polyurea-ceramic composite coating for the leading edge of a wind power blade and a preparation method thereof. Background Art

[0002] Wind turbine blades are a key component of wind turbines. Blades need to work in different environments, and their performance is directly related to the power generation efficiency of the entire system. During operation, wind turbine blades are affected by complex environments and mechanical loads, causing surface damage (cracks, delamination, resin defects, etc.) or structural damage (fiber breakage, kinking, etc.). Surface damage may be caused by erosion by sand, rain, salt spray, hail, and pollutants, or by impacts from small objects. As the damage to the blade surface intensifies, the blade structure will be destroyed, affecting the aerodynamic shape of the blade and causing a decrease in power generation.

[0003] Among them, the leading edge of the blade is the most important part that cuts the wind. When raindrops hit the surface, they can generate great stress, causing cracking of the blade leading edge coating, debonding, cracks in the composite material, and surface roughening. Most domestic blade manufacturers use the method of coating the leading edge of the blade with a polyurethane film to protect the blade surface from rain erosion, but polyurethane materials have the disadvantages of poor resistance to rain erosion, high and low temperature resistance, and weather resistance. In wind farms with harsh conditions, the leading edge protection material of the blade will fail after 3 to 5 years, leading to leading edge corrosion. Therefore, the development of a leading edge protection material with high protection, the ability to decompose the stress of rain impact, and weather resistance is a problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a polyurea-ceramic composite coating for the leading edge of a wind turbine blade and a preparation method thereof, so as to solve the technical problems in the prior art that the leading edge of the blade is prone to cracking, debonding and cracking, and the existing coating materials have poor rain erosion resistance, high and low temperature resistance and weather resistance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A polyurea-ceramic composite coating for the leading edge of a wind turbine blade comprises a polyaspartic acid ester polyurea base material, ceramics and isocyanate; the polyaspartic acid ester polyurea base material is composed of polyether amine, diisocyanate and polyaspartic acid ester resin; the ceramic base material is composed of triethoxysilane, ethoxyphenyl silicone resin, additives and catalysts.

[0007] The mass ratio of the polyaspartic acid ester polyurea base material to the ceramic is: (1-2.1):1.

[0008] A further improvement of the present invention is:

[0009] Preferably, the additive consists of nano titanium dioxide, acrylate, organic amine and dimethyl sulfoxide.

[0010] Preferably, the catalyst comprises octamethylcyclotetrasiloxane and potassium hydroxide, and the mass content of the catalyst in the ceramic is 0.1-0.2%.

[0011] Preferably, the polyetheramine is a mixture of any one or more of polyetheramine M230, polyetheramine M1000 or polyetheramine M2000.

[0012] Preferably, the diisocyanate is a mixture of any one or more of isophorone diisocyanate, hexamethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0013] Preferably, the polyaspartic acid ester resin is a mixture of F420 and F520 in a molar ratio of (4-5):1.

[0014] Preferably, the molar ratio of the polyetheramine to diisocyanate is 1:(1-1.3), and the mass ratio of the polyaspartic acid ester to the polyetheramine is (3-8):1.

[0015] Preferably, the mixing ratio of triethoxysilane, ethoxyphenyl silicone resin and additive in the ceramic is 1:1:1.5; and the mass fraction of the catalyst in the ceramic is 0.1-0.2%.

[0016] A method for preparing a polyurea-ceramic composite coating for the leading edge of a wind turbine blade comprises the following steps:

[0017] Step 1, triethoxysilane, dimethyl sulfoxide and a catalyst are mixed and stirred, ethoxyphenyl silicone resin is added, additives other than dimethyl sulfoxide are added after stirring, and ceramics are obtained after stirring;

[0018] Step 2: Mix the polyetheramine and polyaspartic acid ester resin, dry them, cool them, and fully mix them with the ceramic base material to obtain a mixed system A; add diisocyanate to the mixed system A, add dimethyl sulfoxide to the reaction product after the reaction, obtain a polyaspartic acid ester-ceramic dispersion, and then add isocyanate, and obtain a polyurea-ceramic coating after stirring.

[0019] Preferably, the molar ratio of —NCO in the polyaspartic acid ester dispersion to —NH in the isocyanate is 1.2:1.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention discloses a polyurea-ceramic composite coating for the leading edge of a wind turbine blade. The coating comprises aspartic acid ester polyurea and ceramic. The ceramic has good strength and hardness, and can improve the hardness and toughness of the coating as a whole, and improve the overall anti-rainwater scouring performance of the coating. Specifically, the polyaspartic acid ester polyurea is made of polyetheramine, diisocyanate, polyaspartic acid ester resin and isocyanate as raw materials, and the polyetheramine is a hydrophilic monomer, so that the system has good hydrophilicity, which is conducive to forming a water film on the leading edge surface of the wind turbine blade, and effectively buffering the impact of raindrops on the leading edge of the wind turbine blade. Diisocyanate can extend the chain of the system, which can increase the molecular weight of the product, thereby increasing the solid content of the polyurea base material and improving the stability of the solution. Furthermore, the -NCO group can react with the -NH group on the polyaspartic acid ester to form a urea group, thereby reducing the reactivity of the system. The ceramic is composed of four components: (1) a multifunctional silane coupling agent (component A) to form a dense three-dimensional network cross-linked structure through a sol-gel reaction; (2) a multifunctional silicone resin (component B) can participate in the sol-gel reaction of the silane coupling agent to increase the strength and toughness of the three-dimensional cross-linked structure; (3) functional fillers and additives (component C) including (reinforcement, toughening, thermal conductivity, wear resistance, ablation resistance, etc.) fillers, leveling agents, dispersants, etc. (4) a catalyst, namely potassium hydroxide alkali glue; the ceramic has the characteristics of water resistance, alcohol resistance, wear resistance, scratch resistance, and high temperature resistance. The modified polyaspartic acid ester polyurea is stable. After compounding with the ceramic curing agent, the coating is glossy, strong and tough, has good impact resistance and adhesion, and has low water absorption, and can effectively reduce the rain erosion damage on the wetted surface.

[0022] Furthermore, since polyaspartic acid polyurea reacts rapidly with water, deionized water cannot be used as a solvent for the ceramic base material. The present invention selects dimethyl sulfoxide, a polar organic solvent, as a solvent. After adding a catalyst, the sol-gel reaction in the ceramic base material can be promoted to form a dense three-dimensional network cross-linked structure, which can ensure the stability of the coating after compounding.

[0023] The present invention also discloses a method for preparing a polyurea-ceramic composite coating for the leading edge of a wind turbine blade. The preparation method uses aspartic acid ester polyurea and ceramic for compounding. First, a ceramic base material is prepared. The ceramic base material is used as the internal structure in the cross-linked structure of the polyurea base material, and is mixed with polyether amine and polyaspartic acid ester resin raw materials to fully participate in the polyurea reaction. Finally, the polyurea-ceramic coating is applied to the leading edge of the wind turbine blade to obtain the polyurea-ceramic composite coating. The coating is a coating material with rain erosion resistance, wear resistance and weather resistance. Meanwhile, a corresponding preparation method and application are also provided. The preparation method is flexible and simple to operate and can be mass-produced. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific embodiments:

[0025] The invention discloses a polyurea-ceramic composite coating for the leading edge of a wind turbine blade. The coating comprises a polyaspartic acid ester polyurea base material, isocyanate and ceramics. The ratio of the total mass of polyetheramine, polyaspartic acid ester resin and diisocyanate to the mass of ceramics is (1-2.1):1; wherein the polyaspartic acid ester polyurea base material is composed of polyetheramine, diisocyanate and polyaspartic acid ester resin, and the molar ratio of -NCO in the polyaspartic acid ester polyurea base material to -NH in the isocyanate is 1.2:1. The ceramics are composed of three components, component A, component B, component C and component D, wherein component A is triethoxysilane, component B is ethoxyphenyl silicone resin, component C is an additive, specifically nano titanium dioxide, acrylate, organic amine and dimethyl sulfoxide, and component D is a catalyst, namely potassium hydroxide alkali glue.

[0026] The present invention applies ceramics to the coating system of wind turbine blades for the first time, so that aspartic acid ester dispersion polyurea can be cross-linked with ceramics with a three-dimensional network cross-linked structure, which can improve the hardness and toughness of the entire coating when used, thereby improving the ability of the entire coating to resist rain erosion; aspartic acid ester dispersion polyurea can form a protective film while the overall hardness and toughness are high, further improving its own impact resistance and rain erosion resistance.

[0027] In some embodiments, the diisocyanate is any one or more of isophorone diisocyanate, hexamethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0028] In some embodiments, the isocyanate can be any isocyanate, such as toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI), and the like.

[0029] In some embodiments, the polyetheramine is a mixture of any one or more of polyetheramine M230, polyetheramine M1000 or polyetheramine 2000. Polyetheramine M1000 is preferred.

[0030] In some embodiments, the polyaspartic acid ester resin is a mixture of F420 and F520, wherein the molar ratio of the polyaspartic acid ester resin F420 to the polyaspartic acid ester resin F520 is 4-5:1.

[0031] In some embodiments, the molar ratio of polyetheramine to diisocyanate is 1:(1-1.3)

[0032] In some embodiments, the mass ratio of the polyaspartic acid ester resin to the polyetheramine is (3-8): 1

[0033] In some embodiments, the ceramic is composed of four components: (component A) triethoxysilane; (component B) ethoxyphenyl silicone resin; (component C) nano-titanium dioxide, acrylate, organic amine and dimethyl sulfoxide, wherein nano-titanium dioxide is a reinforcing filler, acrylate is a leveling agent, organic amine is a pH regulator, dimethyl sulfoxide is a solvent, and the mass ratios of components A, B, and C in the ceramic are 1:1:1.5, respectively. Component D is a catalyst, comprising octamethylcyclotetrasiloxane and potassium hydroxide, and the mass content of the catalyst in the ceramic is 0.1-0.2%.

[0034] One embodiment of the present invention discloses a method for preparing a rain erosion protection coating for the leading edge of a wind turbine blade, and the specific steps are as follows:

[0035] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath; 0.2-0.3 parts of potassium hydroxide are slowly added into the beaker through a funnel, and the mixture is heated to 115-120° C. with stirring. After the potassium hydroxide is completely dissolved, the mixture is cooled to room temperature to obtain a transparent potassium hydroxide gel, i.e., catalyst component D.

[0036] (2) Weigh the ceramic components A, B and C respectively, with the mass ratio of the three components in the ceramic being 1:1:1.5, and weigh the catalyst component D in step (8), with the mass content of the catalyst component D being 0.1-0.2%.

[0037] (3) Place the triethoxysilane and dimethyl sulfoxide components A and the catalyst component D in a 50°C water bath and stir for 0.5 to 1 hour at a stirring speed of 100 to 180 r / min.

[0038] (4) Adding component B ethoxyphenyl silicone resin to the reaction product in step (10), stirring at room temperature for 2 to 2.5 hours at a stirring speed of 400 to 560 r / min.

[0039] (5) Add the nano-titanium dioxide, acrylic acid and organic amine in component C to the reaction product of step (11), stir at room temperature for 1 to 1.5 hours at a stirring speed of 400 to 500 r / min to obtain a ceramic base material.

[0040] (6) Weigh the polyetheramine and polyaspartic acid ester resin according to the above ratio respectively, and place them in a four-necked flask for vacuum drying. The vacuum drying conditions are: 100-105°C, -0.04-0.07MPa, and the time is 1-1.5h.

[0041] (7) Weigh the diisocyanate according to the above ratio and place it in a constant pressure titration funnel.

[0042] (8) Weigh the ceramic base material in step (5) according to the above ratio and place it in a constant pressure funnel.

[0043] (9) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) is taken out from the vacuum drying oven, nitrogen is introduced into the flask while turning on the stirrer, and the temperature is lowered to 30-50° C.

[0044] (10) Open the constant pressure funnel in step (8) and add the ceramic base material into the four-necked flask at a constant speed for 0.5 to 1 h.

[0045] (11) Open the constant pressure titration funnel in step (7) and add diisocyanate to the four-necked flask at a constant rate for 1 to 1.5 hours.

[0046] (12) After the dropping is completed, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drop it into the four-necked flask, raise the temperature to 50-70°C, and react at the constant temperature for 2-3 hours.

[0047] (13) Using a constant pressure titration funnel, slowly add dimethyl sulfoxide to the reaction product of step (12) and start stirring. The addition time is 0.5 to 1 h, the stirring speed is 1000 to 1300 r / min, and the stirring time is 0.3 to 0.5 h to obtain a polyaspartic acid ester-ceramic dispersion.

[0048] (14) According to the weight of the reaction product polyaspartic acid ester-ceramic dispersion in step (13), the weight of isocyanate is weighed, and the ratio of the two is calculated as n(-NCO):n(-NH)=1.2:1, and the two are fully stirred and mixed to obtain a polyurea-ceramic coating.

[0049] The coating is applied to a wind turbine blade to obtain a coating.

[0050] Example 1

[0051] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath;

[0052] Slowly add 0.2 parts of potassium hydroxide into the beaker through a funnel, start stirring and heat to 115°C. After the potassium hydroxide is completely dissolved, cool to room temperature to obtain a transparent potassium hydroxide gel, i.e., catalyst component D.

[0053] (2) Weigh the ceramic components A, B and C respectively, with the mass ratio of the three components in the ceramic being 1:1:1.5, and weigh the catalyst component D in step (8), with a mass content of 0.1%.

[0054] (3) Component A triethoxysilane and dimethyl sulfoxide and catalyst component D were placed in a 50°C water bath and stirred for 0.5 h at a stirring speed of 100 r / min.

[0055] (4) Adding component B ethoxyphenyl silicone resin to the reaction product in step (10), stirring at room temperature for 2 hours at a stirring speed of 400 r / min.

[0056] (5) Add the nano-titanium dioxide, acrylic acid and organic amine in component C to the reaction product of step (11), stir at room temperature for 1 hour at a stirring speed of 400 r / min to obtain a ceramic base material.

[0057] (6) Weigh the mixture of polyetheramine M230 and polyaspartic acid ester resin F420 and F520 (ratio of 4:1) respectively, the mass ratio of the mixture of polyetheramine M230 and polyaspartic acid ester resin F420 and F520 is 3:1, and place it in a four-necked flask under vacuum drying conditions of 100°C, -0.04MPa, and time for 1h.

[0058] (7) Weigh isophorone diisocyanate and place it in a constant pressure titration funnel. The molar ratio of polyetheramine to diisocyanate is 1:1.

[0059] (8) Weigh the ceramic base material in step (5), the total mass of the polyetheramine, polyaspartic acid ester resin and diisocyanate and the mass of the ceramic being in a ratio of 1:1, and place the ceramic base material in a constant pressure funnel.

[0060] (9) The four-necked flask containing the polyetheramine and polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 30°C.

[0061] (10) Open the constant pressure funnel in step (8) and add the ceramic base material into the four-necked flask at a constant speed for 0.5 h.

[0062] (11) Open the constant pressure titration funnel in step (2) and add diisocyanate dropwise to the four-necked flask at a uniform rate for 1 h.

[0063] (12) After the addition, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask. Raise the temperature to 50 °C and keep the reaction at this temperature for 2 h.

[0064] (13) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (12) while stirring. The dropping time is 0.5 h, the stirring speed is 1000 r / min, and the stirring time is 0.3 h.

[0065] (14) According to the weight of the reaction product polyaspartic acid ester-ceramic dispersion in step (13), the weight of isocyanate (IPDI) is weighed, and the ratio of the two is calculated as n(-NCO):n(-NH)=1.2:1, and the two are fully stirred and mixed to obtain a polyurea-ceramic coating.

[0066] Example 2

[0067] (1) 100 parts of octamethylcyclotetrasiloxane are placed in a beaker, and the beaker is placed in an oil bath;

[0068] Slowly add 0.3 parts of potassium hydroxide into the beaker through a funnel, start stirring and heat to 120°C. After the potassium hydroxide is completely dissolved, cool to room temperature to obtain a transparent potassium hydroxide gel, i.e., catalyst component D.

[0069] (2) Weigh the ceramic components A, B and C respectively, with the mass ratio of the three components in the ceramic being 1:1:1.5, and weigh the catalyst component D in step (8), with a mass content of 0.2%.

[0070] (3) Component A triethoxysilane and dimethyl sulfoxide and catalyst component D were placed in a 50°C water bath and stirred for 1 h at a stirring speed of 180 r / min.

[0071] (4) Adding the ethoxyphenyl silicone resin of component B to the reaction product of step (10), stirring at room temperature for 2.5 hours at a stirring speed of 560 r / min.

[0072] (5) Add the nano-titanium dioxide, acrylic acid and organic amine in component C to the reaction product of step (11), stir at room temperature for 1.5 hours at a stirring speed of 500 r / min to obtain a ceramic base material.

[0073] (6) Weigh the mixture of polyetheramine M230 and polyaspartic acid ester resin F420 and F520 (ratio of 5:1) respectively. The mass ratio of the mixture of polyetheramine M230 and polyaspartic acid ester resin F420 and F520 is 8:1. Place the mixture in a four-necked flask and place it under vacuum drying conditions of 105°C, -0.07MPa, and the drying time is 1.5h.

[0074] (7) Hexamethylene diisocyanate is weighed and placed in a constant pressure titration funnel. The molar ratio of polyetheramine to diisocyanate is 1:1.3.

[0075] (8) Weigh the ceramic base material in step (5), the total mass of the polyetheramine, polyaspartic acid ester resin and diisocyanate to the mass of the ceramic is 2.1:1, and place the ceramic base material in a constant pressure funnel.

[0076] (9) The four-necked flask containing the polyetheramine and the polyaspartic acid ester resin in step (1) was taken out from the vacuum drying oven, nitrogen was introduced into the flask while the stirrer was turned on, and the temperature was lowered to 50°C.

[0077] (10) Open the constant pressure funnel in step (8) and add the ceramic base material into the four-necked flask at a constant speed for 1 h.

[0078] (11) Open the constant pressure titration funnel in step (2) and add hexamethylene diisocyanate dropwise to the four-necked flask at a uniform rate for 1.5 h.

[0079] (12) After the addition, rinse the constant pressure titration funnel with a certain amount of dipropylene glycol dimethyl ether and drip it into the four-necked flask. Raise the temperature to 70 °C and keep the reaction at this temperature for 3 h.

[0080] (13) Change the constant pressure titration funnel and slowly add dimethyl sulfoxide to the reaction product of step (5) while stirring. The dropping time is 1 h, the stirring speed is 1300 r / min, and the stirring time is 0.5 h.

[0081] (14) According to the weight of the reaction product polyaspartic acid ester-ceramic dispersion in step (6), the weight of isocyanate is weighed, and the ratio of the two is calculated as n(-NCO):n(-NH)=1.2:1, and the two are fully stirred and mixed to obtain a polyurea-ceramic coating.

[0082] Example 3

[0083] In this embodiment, when preparing the polyaspartic acid ester polyurea base material, the polyetheramine used is polyetheramine M1000, and the rest is the same as in Example 1.

[0084] Example 4

[0085] In this embodiment, when preparing the polyaspartic acid ester polyurea base material, the polyetheramine used is polyetheramine M2000, and the rest is the same as in Example 1.

[0086] Example 5

[0087] In this embodiment, when preparing the polyaspartic acid ester polyurea base material, the diisocyanate used is 4,4'-dicyclohexylmethane diisocyanate, and the rest is the same as in Example 1.

[0088] Example 6

[0089] In this embodiment, the mixing molar ratio of F420 and F520 in the polyaspartic acid ester resin is 4.5:1; the mass ratio of the mixture of polyetheramine M230 and the polyaspartic acid ester resins F420 and F520 is 5:1; the rest is the same as in Example 1.

[0090] Example 6

[0091] In this embodiment, the molar ratio of F420 and F520 in the polyaspartic acid ester resin is 4.5:1, and the mass ratio of the mixture of polyetheramine M230 and the polyaspartic acid ester resins F420 and F520 is 6:1. The rest is the same as in Example 1.

[0092] Example 7

[0093] In this embodiment, the molar ratio of polyetheramine to diisocyanate is 1:1.1; the rest is the same as in Embodiment 1.

[0094] Example 8

[0095] In this embodiment, the molar ratio of polyetheramine to diisocyanate is 1:1.2; the rest is the same as in Embodiment 1.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A polyurea-ceramic composite coating for the leading edge of a wind turbine blade, characterized in that: It includes a polyaspartic acid ester polyurea base material, ceramics and isocyanate; the polyaspartic acid ester polyurea base material is composed of polyether amine, diisocyanate and polyaspartic acid ester resin; the ceramics are composed of triethoxysilane, ethoxyphenyl silicone resin, additives and catalysts; The mass ratio of polyaspartic acid ester polyurea base material to ceramic is: (1~2.1):1; The catalyst comprises octamethylcyclotetrasiloxane and potassium hydroxide, and the mass content of the catalyst in the ceramic is 0.1-0.2%; The mixing ratio of triethoxysilane, ethoxyphenyl silicone resin and additive in the ceramic is 1:1:1.

5.

2. The polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 1, characterized in that: The additive consists of nano titanium dioxide, acrylic ester leveling agent, organic amine and dimethyl sulfoxide.

3. The polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 1, characterized in that: The polyetheramine is any one or more of polyetheramine M230, polyetheramine M1000 or polyetheramine M2000.

4. The polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 1, characterized in that: The diisocyanate is a mixture of any one or more of isophorone diisocyanate, hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate.

5. The polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 1, characterized in that: The polyaspartic acid ester resin is a mixture of F420 and F520 in a molar ratio of (4-5):

1.

6. The polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 1, characterized in that: The molar ratio of the polyetheramine to the diisocyanate is 1:(1-1.3), and the mass ratio of the polyaspartic acid ester to the polyetheramine is (3-8):

1.

7. A method for preparing a polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, triethoxysilane, dimethyl sulfoxide and a catalyst are mixed and stirred, ethoxyphenyl silicone resin is added, additives other than dimethyl sulfoxide are added after stirring, and ceramics are obtained after stirring; Step 2: Mix the polyetheramine and polyaspartic acid ester resin, dry them, cool them, and fully mix them with ceramics to obtain a mixed system A; add diisocyanate to the mixed system A, and after the reaction, add dimethyl sulfoxide to the reaction product to obtain a polyaspartic acid ester-ceramic dispersion, and then add isocyanate, and stir to obtain a polyurea-ceramic coating.

8. The method for preparing a polyurea-ceramic composite coating for the leading edge of a wind turbine blade according to claim 7, characterized in that: The molar ratio of -NCO in isocyanate and -NH in polyaspartic acid ester-ceramic dispersion is 1.2:1.

Citation Information

Patent Citations

  • Wind turbine blade leading edge protective coating and preparation method thereof

    CN112143302A

  • Organic silicon modified polyaspartic acid ester coating and preparation method thereof

    CN114410200A

  • Radix asparagi polyurea wind turbine blade gel coat and preparation method thereof

    CN115960525A

Cited By

  • High-performance solvent-free blade wear-resistant self-repairing finish paint and preparation method thereof

    CN120795761A

  • A high-performance solvent-free blade wear-resistant self-healing topcoat and its preparation method

    CN120795761B